(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Parents play a crucial role in the early education of young learners. Their involvement significantly impacts children’s cognitive, social, and emotional development. This article explores how parents contribute to their children’s learning, effective strategies for parental involvement, and the challenges they may face. By fostering a learning-friendly environment, supporting language development, and using engaging teaching methods, parents can enhance their children’s educational success.